Vasopressin and angiotensin receptors of the medial septal area in the control of mean arterial pressure induced by vasopressin - Pavan de Arruda Camargo, Gabriela Maria [UNESP]; Saad, Wilson Abrao [UNESP]; de Arruda Camargo, Luiz Antonio [UNESP] (Sage Publications Ltd, 2008)
Introduction. Brain arginine(8)-vasopressin (AVP), through the V-1a- and V-2-receptors, is essential for the maintenance of mean arterial pressure (MAP). Central AVP interacts with the components of the renin-angiotensin system, which participate in MAP regulation. This study all to determine the effects of V-1a-, V-2- and V-1a/V-2-AVP selective antagonists and AT(1)- and AT(2)-angiotensin II (Ang II) selective antagonists on the MAP induced by AVP injected into the medial septal area (MSA) of the brain.Materials and methods. Male Holtzman rats with stainless steel cannulae implanted into the MSA were used in experiments. Direct MAP was recorded in Conscious rats.Results. AVP administration into the MSA caused a prompt and potent pressor response in a dose-dependent fashion. Pretreatment with the V-1a- and V-2-antagonists reduced, whereas prior injection of the V-1a/V-2-antagonist induced a decrease in the MAP that remained below the baseline. Both AT(1)- and AT(2)-antagonists elicited a decrease, While simultaneous injections of two antagonists were more effective in decreasing the MAP induced AVP.Conclusion. These results indicate there is a synergism bell the V-1a- and V-2-AVP, and AT(1)- AT, and AT(2)-Ang II receptors in the MSA in the regulation of MAP.
Keywords: AT(1)- and AT(2)- receptors; medial septal area; median arterial pressure; V-1a- and V-2-receptors; vasopressin